Qualidade da madeira e da celulose de clones de Eucalyptus spp. de diferentes densidades - Diogo, Fernanda Asti [UNESP] (2014)
The objective of this study was to evaluate the wood and pulp quality of Eucalyptus spp. with differents specific gravities. The materials used were 10 trees of low specific gravity E. grandis clone (0.456 g/cm³) and 10 trees of high specific gravity E. grandis x E. urophylla hybrid (0.510 g/cm³) at 6 years of age. Dendrometric parameters (DBH, total height, commercial height, volume with bark, volume without bark, percentage of bark and commercial volume without bark), physical properties (wood basic density and apparent density of the chip), chemical composition (solubility in NaOH1%, total extractives, lignin and holocellulose), kraft pulp using active alkali 14 and 16% (kappa number, gross income and debugged income, rejects and specific consumption of wood) and the classification of fibers wood were analyzed. Chemically, the materials do not differ from each other. The baking with active alkali 14% resulted in a high kappa number for the two materials. All this cooking results showed a significant difference between the materials, and the high density material was characterized by a higher gross income (57.05%) and debugged (52.52%). In cooking with active alkali 16%, kappa number showed an expected result and the yields did not show a statistical difference between the materials.